An Advanced Holter Monitor Using AD8232 and MEGA 2560 - Zhudiah Annisa; Priyambada Cahya Nugraha; M Ridha Makruf (Jurnal Teknokes, 2021)
Monitoring of cardiac signals is very important for patients with heart disease. The detection of the ECG signal that is carried out for twenty hours will help the doctor to diagnose heart disease. The purpose of this study was to develop a portable ECG monitoring system and cost as it is called a Holter monitor. The main design of ECG module consists of the AD8232, DS3231 RTC module, Arduino microcontroller, and SD card memory. ECG signals are collected from the body of a standard measurement based LEAD II .. To record the raw data from the ECG signal, SD card memory is used to store data for further data analysis. Calibration is performed using a phantom ECG. This is done to make the design results are in accordance with the standard ECG machine.